Zusammen arbeiten Praktiken der Koordination und Kooperation in kollaborativen Prozessen - Groth, Stefan 1982-; Ritter, Christian 1979- (Kultur und soziale Praxis, 2019)
How are forms of cooperation negotiated and organized? Inside views into the concealed logics of collaborative research